Harms Associated with Inhaled Cannabis for Management of Chronic Pain: A Systematic Review and Meta-analysis of Observational Studies - Jomy, Jane (My University, 2022)
Background: Cannabis is increasingly used for management of chronic pain; however, the benefits and harms of this therapy remain uncertain. We conducted a systematic review to inform harms associated with inhaled cannabis for chronic pain. Methods: We searched MEDLINE, EMBASE, PsychInfo, and Web of Science for non-randomized studies reporting on harms associated with inhaled cannabis use, from inception to October 6, 2021. We used random-effects models for meta-analyses and assessed the certainty of evidence using the GRADE approach. Results: We identified 29 eligible studies enrolling 174,562 participants that reported 145 adverse events. Moderate certainty evidence suggests inhaled cannabis use is probably associated with dry mouth (prevalence: 56%; 95%CI 49 to 64), thirst (prevalence: 44%; 95% CI 33 to 55), fatigue (prevalence: 38%; 95%CI 31 to 45), nausea (prevalence: 17%; 95%CI 8 to 27), increased appetite (prevalence: 13%; 95%CI 9 to 18), dizziness (prevalence: 10%; 95%CI 6 to 14), diarrhea (prevalence: 9%; 95%CI 3 to 18), confusion (prevalence: 9%; 95%CI 5 to 13), mood changes (prevalence: 8%; 95%CI 4 to 15), hallucinations (prevalence: 7%; 95%CI 4 to 10), amnesia (prevalence: 6%; 95%CI 3 to 11), impaired coordination (prevalence: 5%; 95%CI 4 to 6), and disorientation (prevalence: 3%; 95%CI 1 to 7). Moderate certainty evidence shows that, compared to non-users, inhaling cannabis is probably associated with increased risk of shortness of breath (risk difference [RD]: 7%; 95%CI 4 to 10). Conclusions: Our review found moderate certainty evidence that dry mouth, thirst, and fatigue are probably frequently experienced with inhaled cannabis use. Several other adverse events are also probable associated with inhaled cannabis use but were less common. Rigorously conducted cohort studies are needed to inform harms associated with inhaled medical cannabis for chronic pain.
Harms Associated with Inhaled Cannabis for Chronic Pain
Keywords: chronic pain; cannabis; harms; systematic review; meta-analysis